Hubungan Pola Asuh Orang Tua dengan Perkembangan Sosial Anak Usia Pra Sekolah di TK Dharma Wanita Persatuan IV Carat Gempol Pasuruan - Eka Yusmanisari (NHM PRESS, 2020)
Children with preschool ages, the growth that is important are cognitive growth, psychosexual, psycho moral, and the one thing is social growth. social growth could be growing well if children have initiative and no guilt. But, if children have feel guilt and less initiative, social growth is not yet success. To avoid problem about social growth on children we are needed parent’s role to care. Parent’s role to care could be given are democratic, permissive, and otoriter. Aid from this research is for knowing the relationship among parent’s role to care with social growth of children with preschool ages on Dharma Wanita Persatuan IV Carat Gempol Pasuruan. Research design that was used is a correlative method with sample 45 respondents. The data was collected from the questioner test, and then the result from the questionnaire would be tabulated and researched, and then presented on the table. From research, 42% of parents are more use democratic, more of them have children with social growth as well as 12 respondents (27%). After the result of the research was tested with a chi square statistic test, we know that there is a relationship among parent’s role to care with social growth of children with preschool ages on Dharma Wanita Persatuan IV Carat Gempol Pasuruan. So, more hoped for parents to always give attention to good parent’s role to care and give good example to act for children, so children’s growth could be success with optimal.